High-Throughput Strategies for the Discovery of Anticancer Drugs by Targeting Transcriptional Reprogramming - Huang, Lijun; Yi, Xiaohong; Yu, Xiankuo; Wang, Yumei; Zhang, Chen; Qin, Lixia; Guo, Dale; Zhou, Shiyi; Zhang, Guanbin; Deng, Yun; Bao, Xilinqiqige; Wang, Dong (Frontiers in Oncology, 2021)
Transcriptional reprogramming contributes to the progression and recurrence of cancer. However, the poorly elucidated mechanisms of transcriptional reprogramming in tumors make the development of effective drugs difficult, and gene expression signature is helpful for connecting genetic information and pharmacologic treatment. So far, there are two gene-expression signature-based high-throughput drug discovery approaches: L1000, which measures the mRNA transcript abundance of 978 "landmark" genes, and high-throughput sequencing-based high-throughput screening (HTS2); they are suitable for anticancer drug discovery by targeting transcriptional reprogramming. L1000 uses ligation-mediated amplification and hybridization to Luminex beads and highlights gene expression changes by detecting bead colors and fluorescence intensity of phycoerythrin signal. HTS2 takes advantage of RNA-mediated oligonucleotide annealing, selection, and ligation, high throughput sequencing, to quantify gene expression changes by directly measuring gene sequences. This article summarizes technological principles and applications of L1000 and HTS2, and discusses their advantages and limitations in anticancer drug discovery.